Vessels with epigraphic and pseudo-epigraphic inscriptions from the territory of the Tsarevskoye settlement - Iudin N.I.; Nuretdinova A.R. (Золотоордынское обозрение)
Research objectives: To study 14th century vessels with epigraphic and pseudo-epigraphic inscriptions. Research materials: Ceramic vessels kept in the Archaeological Museum of Kazan Federal University. Results and novelty of the research: In the 1960s, large-scale archaeological work was carried out on the archaeological sit of Tsarevskoye settlement by the Volga Archaeological Expedition led by G.A. Fedorov-Davydov. A group from Kazan State University (led by I.S. Weiner) also took part in the the expedition. As a result, a large layer of material sources was obtained within which, the most massive example of material was ceramics. To date, archeological objects discovered during the excavations of the Tsarevskoye settlement in 1961–1968 are in the funds of the Archaeological Museum of the Kazan (Volga Region) Federal University. In addition to the artistic merits of the ceramics of the Golden Horde era, these items have a special scientific source-study significance since, being obtained as a result of field research, they are stratified and provided with an archaeological context. As part of the study, five stonepaste-based glazed vessels, one Central Asian stamped jug, and one die for the manufacture of stamped dishes were considered as the main research subjects. Vessels with epigraphic inscriptions meet analogies among the materials of the Lower Volga and Central Asian sites. Thus, the article introduces new data obtained as a result of epigraphic, linguistic, and comparative analyses of the collection originating from the territory of the eastern suburb of Tsarevskoye settlement of the 14th century.